Impact of Islamic film on understanding of Islamic values and cultures for a multiracial society in Malaysia - Wok, Saodah; Ismail, Rizalawati; Abdul Manaf, Faridah (International Journal of Science Commerce and Humanities, 2014)
Religious film plays an import role in educating the viewers, especially the youth. This study tries to compare the results of the experimental group (N=141) to the control group (N=150) on perception of, attitude on, and impact change from watching Islamic film. Specifically, it analyses the effect of an Islamic short film on youth behavioral change, according to race, religion, age and gender. The study uses a quantitative research design, with an experimental research method, using questionnaire as the research instrument for data collection. Results revealed that there were no differences between the experimental and the control group on the overall perception and the overall attitude, but the difference exists for the overall impact change. Surprisingly, the control group assessment on the impact of film, as a whole, is higher than the experimental group, after a short Islamic film was shown to the participants. For the control group, the Malay youth indicated a higher impact change assessment than the Chinese while the Muslim participants indicated a higher impact change assessment than the Christian, Hindus, Buddhist and Others. For the experimental group, the Malay youth gave a higher impact change assessment than either the Chinese or the Indian, with the Muslims superseded the Buddhists, and the least affected age group was the teenagers compared to the adolescents and the young adults. Therefore, the short film was making an impact on the participants, negatively. Thus, Social Learning Theory could be applied to learning of both positive and negative type of information. Suggestions to young film makers are posted so that they make religious films interesting enough, not as a threat, challenging youth existing knowledge on their own faith and on Islam; but as a motivation and reinforcement.